“Plan de marketing social para concientizar los embarazos no deseados en adolescentes del Colegio Experimental Simón Bolívar de la ciudad de Quito” - Sánchez Izurieta, Diana Gabriela (2014)
The research and analysis of this topic, comes from the necessity to find a prevention strategy aimed to control unwanted teenage pregnancies in Simon Bolivar High School, which is located in Quito. According to the information obtained until March 10th 2014, there are 42 teenagers who have already become into mothers and 11 little girls who are pregnant, from a total of 3330 students. Apparently these figures are no so outstanding only equivalent of 1.6% student populationalized; our point of view look to identify the difficult degree about commotion and responsibility witch the students face when challenging unexpected situation their life, as in their families and governmental and institutional authorities.